Branched-Chain Amino Acids and Branched-Chain Keto Acids in Hyperammonemic States: Metabolism and as Supplements - Holeček, Milan (Metabolites, 2020)
In hyperammonemic states, such as liver cirrhosis, urea cycle disorders, and strenuous exercise, the catabolism of branched-chain amino acids (BCAAs; leucine, isoleucine, and valine) is activated and BCAA concentrations decrease. In these conditions, BCAAs are recommended to improve mental functions, protein balance, and muscle performance. However, clinical trials have not demonstrated significant benefits of BCAA-containing supplements. It is hypothesized that, under hyperammonemic conditions, enhanced glutamine availability and decreased BCAA levels facilitate the amination of branched-chain keto acids (BCKAs; α-ketoisocaproate, α-keto-β-methylvalerate, and α-ketoisovalerate) to the corresponding BCAAs, and that BCKA supplementation may offer advantages over BCAAs. Studies examining the effects of ketoanalogues of amino acids have provided proof that subjects with hyperammonemia can effectively synthesize BCAAs from BCKAs. Unfortunately, the benefits of BCKA administration have not been clearly confirmed. The shortcoming of most reports is the use of mixtures intended for patients with renal insufficiency, which might be detrimental for patients with liver injury. It is concluded that (i) BCKA administration may decrease ammonia production, attenuate cataplerosis, correct amino acid imbalance, and improve protein balance and (ii) studies specifically investigating the effects of BCKA, without the interference of other ketoanalogues, are needed to complete the information essential for decisions regarding their suitability in hyperammonemic conditions.
Keywords: exercise; urea-cycle disorders; liver cirrhosis; glutamine; α-ketoglutarate